EKSISTENSI KYMCO MOTOR CLUB BALI DAN EKSPRESINYA SEBAGAI BUDAYA JALANAN DI KOTA DENPASAR - Hari Sankara, Gede (Humanis; Volume 1. No. 2. Desember 2012, 2012)
Implication of modernisation and globalisation on the development of culture, not just the displacement of tradition, but also the emergence of the phonemenon of street culture. Street culture flourished along with modernisation are taking place in the city of Denpasar. In this case, the modernisation not only changed the old into the new, but also defines the things that have properties that are in line with the globalization. For example, the emergence of the fenomenom of street culture, a group of bikers in town with brand kymcodenpasar. This groupofridersb gathered role in anorganisation called Kymco Motorcycle Club Bali. Kmcb revealedtrough the following three problem formulation, (1) how the existence of Kymco Motorcycle Club Bali in the city of Denpasar?, (2) how the expression of Kymco Motorcycle Club Bali the street culture in the city of Denpasar?, (3) how contributions Kymco Motorcycle Club Bali social problems in the city of Denpasar? To answer these three questions use the theory of structural fungtionalism and the theory of symbols. Data collected by observation, interviews, library research, and document analysis. Data is already collected were analysis by descriptive intepretative trough datareduction, data presentation, and verification or inference. At the end of this study revealed the following rights. (1) Kymco Motorcycle Club Bali establish existence trough group activities are strukturally and functionally. (2) expression Kymco Motorcycle Club Bali featuring urban cultural identity which is characterized by the consumption of symbolic, aesthetic transformation and symbolic production arena. (3) Kymco Motorcycle Club Bali positive contribution in tackling social problems in the city of Denpasar, delinquency, traffic order, the development o talents and interests.